(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This article scientifically analyzes the theoretical foundations of linguopragmatics, the stages of its formation and its role in speech activity. It also covers the use of language units in a communicative situation, the relationship between the subject and object of speech, and the mechanisms for the formation of pragmatic meaning.